Quantitative and qualitative differences worth considering in approaching critical infrastructures resilience - Badea, Dorel; Bârsan, Ghiță; Virca, Ioan; Iancu, Dumitru (MATEC web of conferences, 2017)
Through the implicit connections between risk, safety, protection and, last but not least, resiliency, that need to be managed, critical infrastructures have become a subject of increasing interest both for specialists and for academics. Based on this premise, this article analyzes in terms of operational performance several internationally used solutions for assessing resilience, having in view the desire to choose the best in order to be presented in some specialized disciplines of the postgraduate curricula that are annually presented in the educational offer of the Land Forces Academy. The authors also present their own vision on approaching the resilience of critical infrastructures so that it can harmoniously be integrated into the security plans of the holders or operators of such special assets.